The Efektivitas Metode NYAJI (Nyanyi-Ngaji) Terhadap Peningkatan Kemampuan Kognitif Siswa Mata Pelajaran Nahwu - Muhammad Syaifuddin Arif; Ashif Az Zafi; Muhammad Wazid Husni (Prodi Pendidikan Agama Islam, IAIN Sultan Amai Gorontalo, 2025)
The purpose of this study is to evaluate how well the NYAJI method works to enhance students' cognitive abilities and motivation in the Nahwu subjects. The type of research used is quasi-experimental with posttest-only control group design. The study sample consisted of all 10th and 11th students with a total of 466 students. Sampling technique using is random sampling. Data collection techniques were carried out by questionnaires to measure students' learning motivation and test sheet for the cognitive abilities. The data analysis used is Mann-Whitney test for the cognitive abilities. The results of the study was the classes that employ the NYAJI method differ from those that do not in that the former have higher cognitive abilities.